Stress and Deformation Analysis of Existing Underground Pipelines During Soft Soil Consolidation with Prefabricated Vertical Drains and Vacuum Preloading - Adli Ahmad Rizaldy; Herwan Dermawan (Portal: Jurnal Teknik Sipil, 2025)
Abstract — This study evaluates vacuum-assisted soft-clay improvement with Prefabricated Vertical Drains (PVD) and its implications for an in-service buried pipeline along a planned toll-road corridor. A descriptive–quantitative approach with PLAXIS 3D couples ground consolidation and soil–pipeline interaction: PVDs are modeled as line drains on a 1.5 m grid to 22 m depth beneath a permeable sand blanket; a 50 kPa vacuum is applied, and embankment loading is staged in four 1 m lifts (design surcharge 123.6 kPa, vacuum-reduced equivalent ≈ 73.6 kPa, fill height ≈ 4 m). Results show rapid dissipation of excess pore pressure and attainment of ~90% consolidation, with total settlement ≈ 3.10 m by the end of the final dwell (~30 days) and a low residual settlement rate. The pipeline’s peak actions are a bending moment 12.86 kN·m/m, shear 115.4 kN/m, and axial force 2,884 kN/m, producing a governing stress of 381 MPa, safely below the 435 MPa allowable (minimum FS ≈ 1.1). Differential settlement arises from non-uniform loading, with a maximum observed contrast of ~100 mm between loaded and lightly loaded segments.